Pengaruh Fintech P2P Lending, Pembiayaan Bank Syariah, Tenaga Kerja, dan Inflasi terhadap Pertumbuhan Ekonomi Sektor Perdagangan di Indonesia - Karmila Karmila; RR. Tini Anggraeni (Universitas Islam Raden Rahmat, 2026)
The trade sector plays a crucial role in Indonesia's GDP. The growth of this sector heavily relies on the availability of capital and the stability of the economic environment. This capital requirement is largely met through Fintech P2P lending and Islamic Bank Financing. However, determining factors such as the dynamics of Labor absorption, as well as fluctuations in Inflation, need further analysis to optimize the growth rate. This research aims to analyse and test the impact of Fintech P2P lending, Islamic Bank Financing, Labor, and Inflation variables on the Economic Growth of the Trade Sector in Indonesia in the short run and the long run. The analytical method used is the Vector Error Correction Model (VECM) with quarterly and monthly data spanning the 2021-2024 period. The results of this study indicate that in the short run, Fintech P2P lending, Islamic Bank Financing, Labor, and Inflation do not significantly influence the Economic Growth of the Trade Sector in Indonesia. Conversely, in the long run, Fintech P2P lending and Inflation have a negative and significant effect on the Economic Growth of the Trade Sector, while Labor has a positive and significant effect. Meanwhile, Islamic Bank Financing has a positive but non-significant effect on the Economic Growth of the Trade Sector.